2009
DOI: 10.1111/j.1529-8019.2009.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Key opinion leaders: where they come from and how that affects the drugs you prescribe

Abstract: Key opinion leaders (KOLs), also known as thought leaders, are the experts in their field upon whom we depend for original research leading to disease understanding and new therapies. We rely on them to write the articles, author the textbooks, and give the presentations that we absorb to become better dermatologists. KOLs have become intimately entwined with the marketing of pharmaceuticals and medical devices, used not only to lend credibility to claims of efficacy and safety but also to promote anecdotal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 13 publications
(18 reference statements)
1
20
0
Order By: Relevance
“…Our findings indicate that physicians with more years in practice received higher payments from industry, compared with less experienced physicians, which is consistent with the recent findings using the 2014–2016 Open Payments data 18. These findings may reflect the fact that industry is most interested in building relationships with physicians who are experts in their field given that such expertise and experience can be obtained over many years of work in research and/or clinical practice 37. Our finding that physicians who attended elite research medical schools on average, received higher industry payments than physicians who attended less prestigious research medical schools is also a new finding and may reflect these same tendencies.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings indicate that physicians with more years in practice received higher payments from industry, compared with less experienced physicians, which is consistent with the recent findings using the 2014–2016 Open Payments data 18. These findings may reflect the fact that industry is most interested in building relationships with physicians who are experts in their field given that such expertise and experience can be obtained over many years of work in research and/or clinical practice 37. Our finding that physicians who attended elite research medical schools on average, received higher industry payments than physicians who attended less prestigious research medical schools is also a new finding and may reflect these same tendencies.…”
Section: Discussionsupporting
confidence: 91%
“…It is also important to consider precisely who these individuals are, given the prominent role of "thought leaders" in clinical practice, technology diffusion, and pharmaceutical and device marketing. [23][24][25][26][27][28][29] Although we found that a relatively small proportion of all licensed US orthopedic surgeons (4%) were listed as consultants, the possibility remains that this small group of orthopedic surgeons might have a disproportionate effect on national orthopedic practice through professional societies and instruction of orthopedic trainees.…”
Section: Commentmentioning
confidence: 78%
“…Nevertheless, there appears to be a gap between the intended purpose and practice as financial conflict of interests are severely under‐reported in drug trial meta‐analyses and panel guidelines [34] and practitioners very rarely discount for such conflicts when evaluating the evidence base . Besides clinical guidelines formation, narrative review and editorials by key opinion leaders also have a major impact on clinical practice decisions and the medical community in general .An example of the influence of the conflict of interests of key opinion leaders is that although evidence does not support that brand‐name drugs are superior to generic drugs , editorials often counsel against the interchangeability of generic drugs .…”
Section: How the Industry Influences Healthcare Research Strategy Ementioning
confidence: 99%